Difference Between Simpson’s Probability-Based Diversity Index and Lieberson’s Interaction-Based Diversity Index - Masayoshi Oka (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2026)
Simpson’s probability-based diversity index has been widely used in many fields of study (e.g., ecology, economics, and social sciences). However, it has long been criticized for the lack of clear understanding of what is being measured. To address such a concern, the purpose of this study was to explain how Simpson’s probability-based diversity index can be formulated into an interaction-based diversity index (i.e., Lieberson’s interaction-based diversity index) and to highlight the importance of interpretability and decomposability in the measurement of diversity. Population estimates by race and ethnicity in the District of Columbia were used to demonstrate these points. Therefore, population diversity by sociodemographic groups may be conceived as the extent of interaction among two or more mutually exclusive groups. While further considerations are needed for Lieberson’s interaction-based diversity index to be effective in capturing the distributional pattern of population diversity in geographic space (e.g., handling different population sizes and incorporating spatial information), it may provide a new avenue for moving beyond the probabilistic meaning of diversity and for quantifying population diversity by majority or minority groups and/or by different combinations of majority or minority groups (e.g., two-group diversity, three-group diversity, and four-group diversity).